Nanostructured zinc oxide thin film by simple vapor transport deposition. (September 2015) - Athma, P.V.; Martinez, Arturo I.; Johns, N.; Safeera, T.A.; Reshmi, R.; Anila, E.I.
Highlights: Simple vapor transport method is used for the synthesis of nanostructures. Neither vacuum nor catalyst is used for the preparation. Different nano structures (nanorods, tripods, tetrapods, etc.) are formed on a single film. The nano structures so obtained can be used for the fabrication of optoelectronic devices. Highly symmetric planar tripods. Abstract: Zinc oxide (ZnO) nanostructures find applications in optoelectronic devices, photo voltaic displays and sensors. In this work zinc oxide nanostructures in different forms like nanorods, tripods and tetrapods have been synthesized by thermal evaporation of zinc metal and subsequent deposition on a glass substrate by vapor transport in the presence of oxygen. It is a comparatively simpler and environment friendly technique for the preparation of thin films. The structure, morphology and optical properties of the synthesized nanostructured thin film were characterized in detail by using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and photoluminescence (PL). The film exhibited bluish white emission with Commission International d ' Eclairage (CIE) coordinates x  = 0.22, y  = 0.31.